Social Hierarchy of Adult Male Long-tailed Macaques (Macaca fascicularis) in the Madya Area of Pura Agung Pulaki, Bali - Safitri, Mely; Swasta, Ida Bagus Jelantik; Syah, Moh Jafron (CELEBES Agricultural, 2025)
Long-tailed macaques (Macaca fascicularis) live in groups with a social structure consisting of many males and females (multi-male and multi-female), and interactions between individuals such as social activities are strongly influenced by hierarchy. This study aimed to determine the social hierarchy structure of adult male long-tailed macaques (M. fascicularis) and their behavioral profiles in middle area groups in the Pura Agung Pulaki, Bali. Observations were conducted using focal animal sampling and ad libitum sampling methods. The hierarchical structure was observed using three methods, namely the sociometric matrix method, food distribution, and other analyses that support hierarchical determination (non-copulatory mounting, scrotal touching, and combing between males). The highest activities in the middle area group were browsing (17.2%) and moving (17.2%). The hierarchical structure in the middle area group is ordered from the most dominant individual as follows: Ra, Co, Ma, Ku, Cha, Fra, Ka, Ni, In, and Jo. The hierarchical structure in the middle area group is linear. The provision of food bait has been proven effective in determining the social hierarchy structure in long-tailed macaques (M. fascicularis). This study can be used as a basis for the conservation of long-tailed macaques (M. fascicularis) in the Pura Agung Pulaki area.